Tuckman Procrastination Scale (ATPS) : Psychometric Evidence and Normative Data in Secondary School Students from Lima, Peru - Galindo-Contreras, Jhorleny (2022)
This instrumental design study was carried out with the objective of analyzing the psychometric evidence of the ATPS scale and preparing normative data for its application in secondary school students in Metropolitan Lima. There are 429 students from 11 to 18 years old participated, selected through a non-probabilistic convenience sampling. The confirmatory factor analysis of the one-dimensional model with 15 items did not fit, so 5 were discarded, reaching an adequate fit for this re-specified model: X2/gl =1.681, CFI=.992, TLI=.990, RMSEA=.040, SRMR=.030. Also, evidence of convergent validity was found with test anxiety (r = .618) and discriminant validity with academic self-efficacy (r=-.385). The reliability was estimated with the alpha coefficients: α=.85, and Omega: ω=.86). The factorial invariance analysis showed that the test is equivalent by sex and degree of study (∆CFI <.010, ∆RMSEA <.015). Finally, normative data were prepared for the interpretation of ATPS scores in secondary school students from Lima. It is concluded that the ATPS-10 has adequate psychometric properties and has normative data that justify its correct use to measure the levels of academic procrastination in Peruvian secondary school students.